Pengaruh nilai perusahaan pada perusahaan sektor infrastruktur - Sugianti, Anjelina; Amrullah Suwaidi, Rahman (Jurnal Riset Pendidikan Ekonomi, 2025)
Company value has a significant impact on shareholder welfare, because its value reflects the overall success and long-term potential of an investment. Company value is also an important factor in investors' perceptions when choosing a company in which to invest shares. The aim of this research is to empirically test the influence of profitability (ROA), company growth (Asseth Growth), capital structure (DER) and liquidity (CR) on company value. The population of this research is infrastructure sector companies listed on the Indonesian stock exchange in 2020-2023. The sample was taken using a purposive sampling method and obtained 50 companies. The type of data used is secondary data using documentation data collection methods. The analytical method in this research is multiple linear analysis using SPSS. The results of the research show that there is a contribution influence of profitability (ROA), company growth (Asseth Growth), capital structure (DER) and liquidity (CR) on company value.